Analisis Yuridis Penerapan PP Nomor 10 Tahun 1983 Jo. PP Nomor 45 Tahun 1990 terhadap Izin Perceraian bagi Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) di Pengadilan Agama - Efri Refiman; Zulkifli Zulkifli; Sri Yunarti; Elimartati Elimartati; Nofialdi Nofialdi (IDRIS Darulfunun Institute, 2026)
Divorce for Government Employees with Employment Agreements (PPPK) often faces controversy regarding the requirement for a superior's permission letter, although this is not explicitly regulated in national legislation. This study aims to identify and analyze the existence of a superior's permission letter for PPPK in divorce cases and to analyze judges' perspectives on the application of this requirement at the Panyabungan Class II Religious Court. This study used qualitative methods with a field research approach. Primary data were collected through in-depth interviews with five judges (including Chief Justice Dr. Mirwan), court clerks, registration officers, and eighteen PPPK litigants. Secondary data were obtained from official documents such as Chief Justice's Decrees, service brochures, case summaries, and related regulations. Data analysis was conducted using data reduction, data presentation, and conclusion-drawing techniques, while data validity was ensured through source triangulation. The results indicate that court policy requires a superior's permission letter for PPPK at the registration stage as an administrative requirement. However, in court practice, the majority of judges do not consider this a barrier. Of the 18 PPPK cases from 2021 to September 11, 2025, only one case involved a judge actively requesting a permit. There is a sharp difference in the judges' perspectives between the analogy with civil servants and the principle of public welfare versus the principle of legality and the protection of individual civil rights. Normatively, a permit for PPPK is merely an internal administrative policy that is not binding as a legal or formal requirement for litigation. This finding reveals a lack of synchronization between policy and practice, as well as potential legal uncertainty. The study recommends the establishment of clear and uniform national regulations to balance the orderliness of civil servant administration with the right of access to justice for PPPK.